BENTUK KEARIFAN LOKAL PENGELOLAAN AGROFORESTRI DUSUNG DI NEGERI MAMALA KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Raden, Ulmawati; Hatulesila, Jan W.; Bone, Iskar (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This study aims to examine the forms of local wisdom in managing dusung-based agroforestry in Negeri Mamala, Leihitu Sub-district, Central Maluku Regency, as well as to explore its underlying socio-cultural values. The research employed a qualitative method with purposive sampling, involving 30 respondents from five Soa groups, along with key informants such as traditional leaders, village officials, and Soa heads. Data were collected through observation, interviews, questionnaires, literature review, and documentation, and analyzed using the interactive analysis model of Miles and Huberman. The findings reveal that local wisdom in dusung management is reflected through the practices of Sasi and Matakau, which function to conserve natural resources and prevent crop theft. Respondents’ assessment of three local wisdom variables (adaptive-dynamic, harmony with nature, and sustainability-oriented) indicates that the sustainability orientation scored the highest at 40.72% (1,789). Furthermore, the socio-cultural values of the community are embodied in traditional practices such as Bambu Gila, Pukul Sapu, Latupati, and Pela Gandong alliances, which strengthen social solidarity and environmental conservation. This study highlights that dusung management provides not only economic benefits but also cultural preservation and ecological sustainability.